PERANCANGAN CLUSTERING UJIAN ONLINE STUDI KASUS BINA SARANA INFORMATIKA - Sumarna Sumarna (Jurnal Techno Nusa Mandiri, 2015)
A good infrastructure, which can handle hundreds or even thousands of requests from the client and have zero downtime, absolutely necessary by each institution. Clustering is a technique used to improve the performance of a site, whereby using this method, the workload on a site will be divided into any existing server farm behind him. The purpose of this research report is to build a system of clustering and performance tested by performing a stress test cluster and non-cluster. Metologi used in this study is to conduct a needs analysis has been established by the company in the form of a quick response from servers and availability of data (availability). Then the author of designing architecture and implementation of the web server clustering system. Performance of the test has been done, the author concluded that the response time and availability much greater clustering techniques both from a single server.